DYNAMICS OF ADAPTIVE INTERGENERATIONAL SUPERVISION AMONG MILLENNIALS AND GENERATIONS Z NURSES - Ana Zakiyah (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
Generational diversity in nursing practice presents new supervisory challenges in healthcare organizations. Differences in expectations, communication styles, and professional values between Millennial and Generation Z nurses require a more adaptive supervisory approach. This study aimed to explore the perceptions, needs, and relational dynamics of young nurses toward supervisory practices in hospital settings. A qualitative phenomenological design was used with purposive sampling involving 14 nurses from Millennial and Generation Z cohorts. Data were collected through in-depth interviews and analyzed using Collaizi’s method. Five major themes emerged: (1) the meaning of supervision, (2) communication and feedback, (3) responses and adaptive strategies toward supervision, (4) supervisory style and supervisor characteristics, and (5) the impact of supervision on job satisfaction and career development. Generation Z perceived supervision primarily as guidance and quality control, whereas Millennials viewed it as discipline and an indicator of professionalism. Open communication, direct feedback, and democratic leadership were identified as key enablers of work motivation and satisfaction. The findings highlight the need for adaptive intergenerational supervision models that align with contemporary workforce characteristics. This study contributes to the advancement of generation-based nursing supervision theory and provides a foundation for future development of a practical model suited to modern nursing environments.